2020
DOI: 10.1186/s12885-020-6647-4
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy-induced decrease of prognostic nutrition index predicts poor prognosis in patients with breast cancer

Abstract: Background: The prognostic nutritional index (PNI), which is an easily calculated nutritional index, is significantly associated with patient outcomes in various solid malignancies. This study aimed to evaluate the prognostic impact of PNI changes in patients with breast cancer undergoing neoadjuvant chemotherapy (NAC). Methods: We reviewed patients with breast cancer who underwent NAC and a subsequent surgery for breast cancer between 2005 and 2016. PNI before and after NAC were calculated using the following… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 47 publications
2
34
1
Order By: Relevance
“…In this regard, our results provide a novel finding that a decrease in SMI during NAC might have a negative effect on prognosis in patients with breast cancer. Similar to this study, we previously demonstrated that a decrease in PNI during NAC for patients with breast cancer was associated with worse prognosis, but not pretreatment PNI [ 3 ]. Furthermore, other studies have shown that changes in NLR during NAC correlated with the efficacy of NAC and patient survival [ 38 40 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In this regard, our results provide a novel finding that a decrease in SMI during NAC might have a negative effect on prognosis in patients with breast cancer. Similar to this study, we previously demonstrated that a decrease in PNI during NAC for patients with breast cancer was associated with worse prognosis, but not pretreatment PNI [ 3 ]. Furthermore, other studies have shown that changes in NLR during NAC correlated with the efficacy of NAC and patient survival [ 38 40 ].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, NAC allows the evaluation of dynamic changes in the systemic conditions of patients who have a primary tumor during treatment . We previously demonstrated that a decrease in the prognostic nutritional index (PNI), which represents systemic nutritional and immunological status, during NAC had a prognostic impact in patients with breast cancer [ 3 ]. Hence, NAC may have the potential to provide other prognostic markers with respect to changes in patients’ status during treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high decrease in PNI during neoadjuvant chemotherapy predicts a poor prognosis. Maintaining nutritional status during neoadjuvant chemotherapy might lead to better treatment outcomes for the patients with breast cancer (12). Therefore, SII and PNI are prognostic indicators worthy of investigation in MB.…”
Section: Discussionmentioning
confidence: 99%